The ecology of Patella - Branch, George M (Department of Biological Sciences, 2023)
The present thesis is aimed principally at the population dynamics and biological interactions of Patella species. Most of the work is based on all eleven of the South African species, although volume of work necessitated the omission of the less common species from parts of the work. The research has been centred around the juveniles and adults, although it is realised that larval biology is logically the next field which needs to be explored. The thesis is presented as a series of separate papers, the first in published form and the remainder in manuscript, and is concluded by a resume. A single supporting paper is also included. The entire thesis is based on original work by the candidate, except where acknowledged in the text. The more important conclusions are summarised at the end of each section.